Optimization of a 6-DOF Platform for Simulators Based on an Analysis of Structural and Force Parameters - Tatiana Duyun; Ivan Duyun; Petr Kabalyants; Larisa Rybak (Machines, 2023)
Automotive driving simulators are widely used in driving schools and training centers, where they help students acquire the necessary skills without risk to life and health. This paper presents modern research in the field of creating a model and a real prototype of an automotive driving simulator based on the Gough–Stewart platform. This investigation presents optimized geometric parameters using the PSO algorithm. Virtual prototypes of the robotic platform were created by MSC Adams. In turn, this made it possible to conduct the simulation of kinematic and dynamic parameters. They represent operating conditions when exposed to workloads. This paper shows a prototype of an automotive driving simulator and special equipment with an integrated system of virtual 3D models of real terrain.